Sodium Valproate in Migraine Prevention: Efficacy is the same as Propranolol - Chowdhury, MI; Anwar, AKM Ullah; Omar, KM Hassan; Majumder, S (Journal of Armed Forces Medical College, Bangladesh, 2013)
DOI: http://dx.doi.org/10.3329/jafmc.v8i2.16352 JAFMC Vol.8(2) 2012 pp.32-38